Pengaruh Gaya Hidup, Citra Merek, Brand Trust dan Celebrity Endorsment terhadap Keputusan Pembelian - Tita Hartina Azizah; Arinastuti Arinastuti; Ady Achadi (Prosiding Seminar Nasional Ilmu Ekonomi dan Akuntansi, 2024)
This research is based on the existence of a gap phenomenon in the form of differences in research results for each variable, then there is a gap phenomenon in the form of observations of 50 skincare user respondents in Purwokerto showing that Skintific will be ranked 2nd after MS GLOW in 2023. The aim of this research is to analyze the influence of style. life, brand image, brand trust and celebrity endorsement on purchasing decisions for skincare products in Purwokerto. The population in this research is scientific consumers who buy and use in Purwokerto with a sample of 100. The data analysis method used is multiple linear regression and hypothesis testing using t test calculations. The results of this research show that Lifestyle, Brand Image, Brand Trust and Celebrity Endorsement influence purchasing decisions. From the results of this research it can be implied that skincare skintific needs to innovate its products, increase branding in the community by endorsing influencers, and provide real evidence of quality. skincare skintific.